decree of the president of the Arab republic of Egypt no 25/2016 Amending The Harmonized Customs Tariff = قرار رئيس جمهورية مصر العربية رقم 25 لسنة 2016 بتعديل التعريف الجمركية المنسقة Presidency - Egypt. Presidency (2025)
Decree of the President of the Arab Republic of Egypt No. 25 of the year 2016 amending the Harmonized Customs Tariff – قرار رئيس جمهورية مصر العربية رقم 25 لسنة 2016 بتعديل التعريفة الجمركية المنسقة